The effects of caloric restriction and its mimetics in Alzheimer's disease through autophagy pathways. Issue 2 (18th February 2020) - Yang, Yi; Zhang, Lihui
Abstract : AD is a neurodegenerative disease that commonly occurs among older individuals. Caloric restriction and its mimetics have been shown to alleviate amyloid burden, tau pathology, and improve cognitive function of rodent models of AD by activating autophagy. Abstract : Alzheimer's disease (AD) is a neurodegenerative disorder that commonly occurs among older individuals. Increasing evidence suggests that a low-caloric diet might be a promising adjuvant therapeutic strategy for slowing or preventing the pathogenesis and progression of AD through the induction of autophagy. Several intracellular pathways have been implicated in caloric restriction (CR)-induced autophagy. In this review, we summarized the efficacy of CR as well as its mimetics (resveratrol, spermidine, aspirin, rapamycin, metformin, and curcumin) in improving cognitive function of rodent models of AD. On the basis of recent in vitro and animal studies, the beneficial effects of CR- or caloric restriction mimetics-induced autophagy in alleviating amyloid burden and tau pathology of AD were also discussed.